Hardware-in-the-loop simulation for automatic rack and pinion steering system - Mohammad Nasir, Mohd Zakaria; Dwijotomo, Abdurahman; Abdullah, Mohd Azman; Hudha, Khisbullah (2012)
Vehicle handling behaviour is much influenced by the performance of steering system and its mechanism. In this paper, a Hardware-in-the-loop Simulations (I-IILS) test rig has been set up with Matlab XPC TARGET environment, LVDT and rotary encoder sensors installed onto actual rack and pinion steering mechanism, for data measurement at various steering angle. It can manipulate the steering mechanism with various control structure, decrease time with real experiment and trial risk as well as improve development efficiency. Results from experimental model demonstrate a linear pattern occurred from maximum lock-to-lock steering wheel angle and it is closely follow the sine input trend through HILS experiment with acceptable error.